A policy-based management architecture for active and programmable networks. - Tsarouchis, C.
Next generation networks must be capable of supporting a multitude of service providers that exploit an environment in which services are dynamically deployed and quickly adapted over a common heterogeneous physical infrastructure, according to varying and sometimes conflicting customer requirements. In this context, network management must become more flexible in order to cope with these emerging conditions. More specifically, new management architectures must offer service providers the freedom to manage their services according to their own policies and seamlessly extend management functionality as the only way to react to the introduction of new services. Based on a new business model that describes such an environment, we propose a policy-based management architecture that is extensible and operates in an active and programmable network. This management architecture is part of a new network architecture that was developed in the FAIN European Union research and development IST project.
Keywords: European Union; FAIN research and development IST project; Future Active IP Networks; Active networks; Business model; Extensible architecture; Network management; Next generation networks; Policy-based management architecture; Programmable networks; Service providers